Analisis Ranah Kognitif Taksonomi Bloom Revisi pada Soal Ujian Sekolah Bahasa Jawa - Astuti, Fitriyani (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2021)
The purpose of this research is to describe the analysis of the cognitive domain classification revised Bloom’s taxonomy on the Javanese language exam questions for class XII SMAN 1 Kasihan for the 2019/2020 academic year. This research is qualitative research. The research method used is descriptive research. The source of the research data was the text of the Javanese language exam questions for class XII SMAN 1 Kasihan for the 2019/2020 academic year. Data collection was using documentation study techniques. The data analysis technique is matching the questions with the criteria of the cognitive domain of the revised Bloom’s taxonomy. The research results showed that the analysis of the classification of the cognitive domains was: remembering-C1, understanding-C2, applying-C3, analysing-C4, evaluating-C5, and creating-C6. There are 5 items or 2.25% of remembering classification (C1), 10 items or 4.5% of understanding classification (C2), 23 items or 10.35% of applying classification (C3), 4 items or 1.8% of analyzing classification (C4), 2 items or 0.9 of evaluating classification (C5), and 1 item or 0.45% of creating classification (C6). Thus, the cognitive domain in the Javanese language exam questions for class XII SMAN 1 Kasihan for the 2019/2020 academic year includes: remembering, understanding, applying, analyzing, evaluating, and creating.